2021
DOI: 10.1021/acs.macromol.1c01346
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-Polyelectrolyte-Based Robust Anion Exchange Membranes via Acetalation of a Commodity Polymer

Abstract: Metallo-polyelectrolytes have been demonstrated to be promising candidates for anion exchange membranes (AEMs) due to their excellent alkaline stability. Here, cobaltoceniumcontaining metallo-polyelectrolyte-based AEMs with good chemical stability and dimensional stability were prepared through facile acetalation of a commodity polymer, poly(vinyl alcohol). The AEM crosslinked with 1 wt % glutaraldehyde (GA) exhibits a comparable hydroxide conductivity of 72 mS/cm at 80 °C and enhanced alkaline stability in 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 64 publications
2
18
0
1
Order By: Relevance
“…1 H NMR (400 MHz, DMSO-d 6 , δ, ppm): 1.56 (m, 2H), 1.98 (t, 2H, J = 5.6 Hz), 2.13 (q, 1H, J = 4.8 Hz), 2.79 (s, 2H), 4.80 (q, 2H, J = 11.2 Hz), 4.99 (d, 4H, J = 13.2 Hz), 5.33 (m, 1H), 5.65 (s, 10H), 5.97 (t, 4H, J = 2.0 Hz), 6.08 (q, 1H, J = 3.2 Hz), 6.13 (q, 1H, J = 2.8 Hz), 6.40 (t, 4H, J = 2.0 Hz), 8.73 (d, 2H, J = 8.0 Hz). 19 The characterization of membrane structure, ion exchange capacity, and ionic conductivity was consistent with our previous report, 49 which is illustrated in the Supporting Information.…”
Section: Synthesis Of Cobaltocenium-containing Monomer M3supporting
confidence: 89%
See 3 more Smart Citations
“…1 H NMR (400 MHz, DMSO-d 6 , δ, ppm): 1.56 (m, 2H), 1.98 (t, 2H, J = 5.6 Hz), 2.13 (q, 1H, J = 4.8 Hz), 2.79 (s, 2H), 4.80 (q, 2H, J = 11.2 Hz), 4.99 (d, 4H, J = 13.2 Hz), 5.33 (m, 1H), 5.65 (s, 10H), 5.97 (t, 4H, J = 2.0 Hz), 6.08 (q, 1H, J = 3.2 Hz), 6.13 (q, 1H, J = 2.8 Hz), 6.40 (t, 4H, J = 2.0 Hz), 8.73 (d, 2H, J = 8.0 Hz). 19 The characterization of membrane structure, ion exchange capacity, and ionic conductivity was consistent with our previous report, 49 which is illustrated in the Supporting Information.…”
Section: Synthesis Of Cobaltocenium-containing Monomer M3supporting
confidence: 89%
“…The chloride conductivity of P2-18Co AEM decreased compared with P2 under a given IEC, which may result from the dispersed ion clusters by the introduction of unfunctionalized norbornene . In addition, all of these AEMs showed an Arrhenius behavior between 30 and 80 °C (Figure B), and the corresponding activation energy of E a was 22.1, 20.4, and 21.8 kJ mol –1 for P1 , P2 , and P3 , respectively, where the E a value was close to those of previous cobaltocenium-containing AEMs. , These results indicated that P2 -based AEM had the highest chloride conduction efficiency, and Cl – in P2 can transport with less activation energy compared with the other two membranes …”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…A landmark solid electrolyte, Nafion, possesses a macromolecular structure with a hydrophobic backbone and a hydrophilic side chain containing sulfonic groups, which can form continuous proton-conducting pathways to achieve a high proton conductivity . In contrast to traditional organic polyelectrolytes, metallopolymers containing multiple charged groups make up a class of inorganic hybrid polyelectrolytes. As previously reported, rational design and careful synthesis can be used to construct useful hybrid polyelectrolytes and optimize their properties and performances for the manufacture of new functional materials …”
Section: Introductionmentioning
confidence: 99%